Pemanfaatan Sarana dan Prasarana Media e-Learning atau Virtual Laboratory dalam Pembelajaran Jarak Jauh di Era Pandemi Covid-19 - Sukenda Sukenda; Ari Purno Wahyu; Benny Yustim; Helmy Faisal Mutaqien; Ulil Surtia Zulpratita (Jurnal Pengabdian kepada Masyarakat Nusantara, 2022)
Training activities, one of the community service activities, vocational high school teacher training activities. The purpose of the training is to provide an overview of learning subjects using e-learning or virtual laboratories. It is hoped that the training will take the form of learning and the learning process will be carried out with online learning during the covid-19 pandemic. The training discussed about e-learning or virtual laboratory learning to Vocational High School teachers. This model has the aim that competence in the field of learning and practice is carried out well. Learning development using online media, virtual laboratory is a practical learning media that is carried out online. E-learning, learning subjects using information technology media. The ability to manage and use e-learning and virtual laboratories is required in distance learning (PJJ). The development of distance learning or online is the right step in using e-learning or virtual laboratories in the covid-19 pandemic era.